2016
DOI: 10.3390/ijms17101709
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effect of Pretreatment with Acenocoumarol in Cerulein-Induced Acute Pancreatitis

Abstract: Coagulation is recognized as a key player in inflammatory and autoimmune diseases. The aim of the current research was to examine the effect of pretreatment with acenocoumarol on the development of acute pancreatitis (AP) evoked by cerulein. Methods: AP was induced in rats by cerulein administered intraperitoneally. Acenocoumarol (50, 100 or 150 µg/kg/dose/day) or saline were given once daily for seven days before AP induction. Results: In rats with AP, pretreatment with acenocoumarol administered at the dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 49 publications
4
24
0
Order By: Relevance
“…Acute pancreatitis stimulates intravascular coagulation with formation of thrombi within blood vessels and coagulation disorders may be in the range between scattered intravascular thrombosis in pancreatic microcirculation to severe disseminated intravascular coagulation [ 84 ]. Moreover, animals and clinical studies showed that treatment with heparin or anticoagulants inhibits the development of acute pancreatitis and accelerates the recovery in this disease [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. These findings indicate that disorders of coagulation play the important role in acute pancreatitis and these disorders may be responsible for the lack of significant improvement in pancreatic blood flow in animals treated with ghrelin despite improved histology of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis stimulates intravascular coagulation with formation of thrombi within blood vessels and coagulation disorders may be in the range between scattered intravascular thrombosis in pancreatic microcirculation to severe disseminated intravascular coagulation [ 84 ]. Moreover, animals and clinical studies showed that treatment with heparin or anticoagulants inhibits the development of acute pancreatitis and accelerates the recovery in this disease [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. These findings indicate that disorders of coagulation play the important role in acute pancreatitis and these disorders may be responsible for the lack of significant improvement in pancreatic blood flow in animals treated with ghrelin despite improved histology of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…In harmony with those findings is the observation that the inhibition of coagulation by pretreatment with low doses of acenocoumarol, a vitamin K antagonist, exhibits a protective effect on the pancreas and inhibits the development of acute pancreatitis induced by ischemia/reperfusion [19] or cerulein [20]. However, from a clinical point of view, it is more important to determine whether the administration of acenocoumarol after the development of acute pancreatitis exhibits any therapeutic effect on this disease.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, the treatment with acenocoumarol improved pancreatic blood flow [ 26 ]. These observations were further confirmed in a rodent model of rats with cerulean-induced AP [ 27 ]. Surprisingly, acenocoumarol seems to be effective not only in AP management, but even in the prevention of disease.…”
Section: Discussionmentioning
confidence: 63%